Analisis Sistem Pemerintahan Sultan Hasanuddin Dalam Perspektif Collaborrative Governance - Andi Mallarangen (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
This research aims to understand Sultan Hasanuddin's policies in establishing collaboration and diplomacy during his rule in the Kingdom of Gowa. The research employs a qualitative research method, specifically literature review, by collecting data from relevant books, journals, and theses related to the topic under investigation. The findings of the research indicate that through collaboration and diplomacy, Sultan Hasanuddin successfully forged strong relations with neighboring kingdoms and countries, particularly in the context of free trade in maritime activities. The collaborative governance approach implemented by Sultan Hasanuddin reflects a strong commitment to cross-sector cooperation, involving various stakeholders, including the government and the community.